Inovasi Pembelajaran PAI melalui Integrasi Nilai-Nilai Digital Citizenship dalam Mentoring Adab - Muharromah, Fityatul; Subando, Joko (Lembaga Yasin AlSys, 2025)
The advancement of digital technology necessitates the transformation of Islamic Education (Pendidikan Agama Islam, PAI) to cultivate students who not only understand Islamic values but also possess wise and responsible digital competencies. This study aims to describe an instructional innovation in PAI through the integration of digital citizenship values within an adab (Islamic ethics) mentoring program. A literature review method was employed to analyze relevant sources on PAI instructional innovation, the concept of digital citizenship, and adab mentoring practices. The findings indicate that incorporating the nine elements of digital citizenship, namely digital access, digital commerce, digital communication, digital literacy, digital etiquette, digital law, digital rights and responsibilities, digital health and wellness, and digital security into the adab mentoring program enhances both students’ understanding of Islamic values and their religious digital literacy. This innovation has demonstrated a positive impact on shaping students’ character to be courteous, ethical, and responsible in digital environments. The findings underscore the urgency of adaptive PAI instruction in the digital age to prepare a generation of Muslims with integrity, both in physical and virtual spaces.